Managing Excess CapacityManaging Excess Capacity, edited by Baden-FullerCharles. Oxford: Basil Blackwell, 1990, 263 pp., cloth. - McGahan, A. M. (Academy of Management Review, 1992)
In this article the authors respond to comments made about a paper they published in a pervious issue that discussed that examined organizational decline. The authors proposed two models of the process in their original work, the second of which drew the most scrutiny. In this article they reexamine this model of organizational decline and address various aspects of the model more intensively. The main areas that they focus on are explaining why administrative ratios were not included in their model as well as offering a better argument for why the assumption of symmetry between decline and growth was not needed in their model.